Problems and puzzles in echinoderm demography - Ebert, Thomas A. (2021)
Introduction: There are problems and puzzles in understanding reproduction, growth and mortality in echinoderm life cycles. Objective: Explore problems and puzzles in life cycles that are important and challenging. Methods: The literature is used to elucidate problems associated with all life stages. Results: Sources of larvae that settle at a site are explored using oceanographic modelling and genetic methods. There are few studies that have estimated larval mortality in the plankton under field conditions and results differ from experimental results or patterns of settlement. In a small number of studies, mortality rate of newly settled larvae appears to change rapidly as individuals grow. There are problems measuring size, and measurement bias that interferes with many tagging methods used to estimate growth. There also are problems with the use of natural growth lines and commonly used software to estimate both growth and mortality from size-frequency data. An interesting puzzle is that echinoderms may show negative senescence with mortality rate decreasing with size. There is a problem in fertilization success based on density so there should not be rare species where sexes are separate with free spawning of gametes yet there seem to be rare echinoderms. Conclusions: All parts of echinoderm life cycles provide problems and puzzles that are important and challenging.